Internalization of Al-Ghazali's Theology in Shaping Santri Character: Analysis Study of the Tarbiyatus Salafiyah Islamic Boarding School in Probolinggo - kustiana arisanti; Ahmad Khumaidi (Pendidikan Agama Islam, Fakultas Ilmu Tarbiyah dan Keguruann, IAIN Syekh Nurjati Cirebon, 2024)
Since its inception, Islamic boarding school education has had distinctive characteristics and continues to maintain its existence even when facing the dynamics of life in this modern era. Without changing its characteristics, which are always identified with the priority of religious, cultural, and social values in its education system, Islamic boarding schools carry out transformations in various fields, including instilling religious character in their students. This holistic education system can ultimately give birth to a generation of students or students who have figures who have morals or good character. One of the Islamic boarding schools that still applies this system is the Tarbiyatussalafiyah Islamic boarding school Tegalsiwalan Probolinggo. This research is aimed at finding out the process of applying Imam Ghazali's theological thinking in shaping the character of students at the Tarbiyatussalafiyah Islamic Boarding School. The approach taken in this research uses a qualitative descriptive approach with a case study type of research. The data sources obtained by researchers were primary sources in the form of information from Islamic boarding school leaders, ustadz, administrators, and students. The research results obtained by researchers in the field in the form of character formation material include: Religious knowledge, physical education, and spirituality. Meanwhile, the implementation process carried out by caregivers, ustadz, and administrators of the Tarbiyatussalafiyah Islamic boarding school in forming the character of the students is by applying three methods, namely the exemplary method, the habituation method, and instilling character values including (1) Performing congregational prayers, (2) Instilling an honest attitude, (3) Discipline, (4) Politeness, (5) Patience, (6) Tolerance.Keywords: Internalization, al-Ghazali, Santri Character, Ayyuhal Walad.